The maintenance of an inversion polymorphism in Coelopa frigida - Butlin, Roger Kenneth (1983)
The seaweed fly, Coelopa frigida, lives in piles of rotting seaweed deposited on beaches by tides and winds. In all populations studied it is polymorphic for two gene arrangements on Chromosome I. A polymorphism at the alcohol dehydrogenase locus is strongly associated with this inversion and can be used to estimate karyotype frequencies. An extensive series of samples from natural populations has revealed a seasonal cycle in inversion frequencies but otherwise frequencies are remarkable constant both geographically and temporally. There is a consistent excess of heterokaryotypes in these samples. Three selective forces influencing inversion frequencies have been investigated. 1) An association between karyotype and development time, previously observed in the laboratory, has been demonstrated in conditions case to those in natural populations. 2) Viability differences between karyotypes have been examined. In natural populations there is some evidence that the excess of heterokaryotypes increases with larval density. In the laboratory heterokaryotypes are shown to have higher viability than either homokaryotype but the strong density dependence reported previously has not been observed. Viability differences are concentrated in the first two days of larval life and are probably related to the rate of supply of nutrients. 3) An association is demonstrated between karyotype and adult size – especially in males. Adult size is shown to correlate with longevity and fecundity of both sexes. Several experiments indicate that large males enjoy greater mating success than small males. The relationship between larval density, development time and adult size is described. The possibility that the effect of the inversion varies between populations or between alcohol dehydrogenase genotypes has also been investigated. A simulation has been used to study how these selective forces interact with one another, and with the changeable environment in which the flies live, and to examine the extent to which they can account for the observed karyotype frequencies.